ALMA Spectral Survey of an Eruptive Young Star, V883 Ori (ASSAY). II. Freshly Sublimated Complex Organic Molecules in the Keplerian Disk - Jae-Hong Jeong; Jeong-Eun Lee; Seonjae Lee; Giseon Baek; Ji-Hyun Kang; Seokho Lee; Chul-Hwan Kim; Hyeong-Sik Yun; Yuri Aikawa; Gregory J. Herczeg; Doug Johnstone; Lucas Cieza (The Astrophysical Journal Supplement Series)
We present an investigation of complex organic molecules (COMs) in the spatially resolved Keplerian disk around V883 Ori, an eruptive young star, based on a spectral survey carried out with the Atacama Large Millimeter/submillimeter Array in Band 6 (220.7−274.9 GHz). We identified about 3700 molecular emission lines and discovered 23 COMs in the disk. We estimated the column densities of the COMs detected, using the iterative LTE line-fitting method. According to our analyses, using only optically thin lines is critical to deriving the reliable column densities of COMs. Therefore, covering a large frequency range is important for the studies of COMs. The most distinct phenomenon found from the spectra of the V883 Ori disk is that nitrogen-bearing COMs other than CH _3 CN are missing, whereas various oxygen-bearing COMs, except for the CH _2 OH-bearing molecules, are detected. The missing CH _2 OH-bearing COMs may indicate the warm water-ice dominant environment for forming COMs. We compared our results with various objects in different evolutionary stages, from Class 0 hot corinos to a solar system comet 67P/Churyumov-Gerasimenko, to examine the effect of evolution on the COM compositions. In general, the COM abundances relative to methanol in V883 Ori are higher than in the hot corinos and hot cores, while they are comparable to the cometary values. This may indicate the planet-forming material chemically evolves in the disk midplane after being accreted from the envelope. In addition, as found in the comet 67P/Churyumov-Gerasimenko, nitrogen might also be trapped as ammonium salt within the dust grains in the V883 Ori disk.